Introduction to accounting : an integrated approach - Ainsworth, Penne; Deines, Dan S. (McGraw-Hill Irwin, 2011)
"The Sixth Edition of Introduction to Accounting: An Integrated Approach revolves around three major themes: The overriding theme of the text is that accounting is an information system that serves many stakeholders, some internal and some external to the organization. The second theme is business processes. The final theme is the balanced scorecard"--Provided by publisher